Volumetric monitoring of cutaneous leishmaniasis ulcers: can camera be as accurate as laser scanner?. Issue 5 (2nd November 2019) - Zenteno, Omar; González, Eduardo; Treuillet, Sylvie; Valencia, Braulio M.; Castaneda, Benjamin; Llanos-Cuentas, Alejandro; Lucas, Yves
ABSTRACT: Cavity volume is an important clinical index for the assessment of the healing process and effectiveness of treatment applied on chronic ulcers. Recently, 3D scanners have proven to effectively track ulcer's volume evolution. However, photogrammetry presents itself as a low cost and portable alternative. We conducted a comparative study between photogrammetric and 3D scanner-based volume estimation of small skin ulcers. A total of 24 cutaneous leishmaniasis ulcers' virtual models were generated using a commercial laser scanner and a full-HD portable camera. The reconstruction from videos was performed using open-source software (VisualSFM). The results revealed a similar performance when compared to 3D Scan-based volume estimation with a median deviation and percentile error of 33.68 mm 3 and 21.10%, respectively. In addition, the method proved to effectively follow the same tendency in the assessment of healing ulcers when compared to the 3D-scanner. Moreover, when comparing the two virtual models trough residual differences after ICP registration the mean error and standard deviation was 0.36 ± 0.27 mm.